Anaesthetic Management of a Giant Cervico-Occipital Meningocele with Cleft Palate - Mansi Jain; Niti Dalal; Charu Bamba (Academia Anesthesiologica International, 2020)
Meningocele is herniation of meninges and CSF through the skull and vertebral defect. The major anaesthetic challenges encountered in management of cervico-occipital meningocele include difficulty in securing airway, proper positioning of the neonate without pressure on the meningocoele sac, maintaining prone position and prevention of electrolyte disturbances and hypothermia. Associated congenital anomalies also can cause anaesthesia and procedure related complications. We report a case of 25 day old neonate with giant cervico occipital meningocele with cleft palate posted for excision and repair.